The Contribution of Fashion Show Activity to Improve Self-Confidence of Children Age 5-6 Years in TK Al Azzam Jatisari Mijen - Wulandari, Diah; Dewanti Handayani, Sri Sularti (Jurusan PGPAUD FIP UNNES, 2021)
This study aims to increase the confidence of children aged 5-6 years through fashion show activity in children of group B Al Azzam Kindergarten Jatisari Mijen, Semarang. Academic Year 2018/2019. This research is expected to be useful, especially in contributing to the development of early childhood education. This type of research is Experimental Research. The research subjects are children aged 5-6 years in group B in Al Azzam kindergarten as many as 31 children. The object of this research is children's confidence which includes being confident in themselves, not dependent on others, feeling valuable, and having the courage to act. The data collection method is done through observation and documentation. Data analysis techniques in this study used the Paired Sample t-Test technique. The results showed that fashion show activity can increase children's confidence. This can be proven from the results of observations before the action obtained a percentage of confidence of 35.29% and in the subsequent implementation increased to 82.35%. The process of implementing learning using fashion modeling activities begins with the teacher explaining the activities to be carried out by the child. Then the teacher gives an example of a fashion show. After giving an example, the teacher invites children who will be modeling clothes to show their hands first. Each child shows in the front, and when difficulties in conveying their meaning the teacher stimulate by asking questions. After the fashion show, each child is given a different question by the teacher. As a form of reinforcement, children are given rewards in the form of praise, cheers, thumbs, applause, and stickers.